Drug Development Life Cycle - Akhtar, Juber; Ahmad, Mohammad; Irfan Khan, Mohammad (IntechOpen, 2022)
Drug authentication is generally governed by critical procedures. This book presents a comprehensive overview of drug design, highlighting the steps involved from the discovery phase to product approval. Chapters address such topics as drug development processes, pharmaceutical nanoformulations and cosmeceuticals for topical use, ocular drug delivery systems, and drug development involving computer-aided drug design, machine learning, and artificial intelligence.